Low latency Path Aware XY-X Routing Algorithm for NoC Architectures - Rao Musala, Venkateswara; V Rama Krishna, T (International Journal of Engineering and Technology, 2018)
Route specific information with the SoC needs a great deal of wiring, which increases the Resistance & Capacitance (RC) component of the system. Network on Chip (NoC) is utilized as the interface to address the problems in SoC, On-chip interconnection network in NoC has gained more consideration over steadfast wiring and buses, like lower latency, scalability and high performance. Present routing algorithms in NoC is suffered from load balancing at incarnation networks under non-uniform traffic conditions, causes increase the NoC trade-offs (latency and throughput). Adaptive routing is a technique to progress the load balance, but previous adaptive routing techniques used uniform traffic patterns to form the routing decisions. This paper proposes a new approach at non- uniform traffic patterns in channel state and path specific, Path Aware Routing (PAR XY-X) uses a timeout piggybacking for acknowledgement and load shedding to avoid congestion which choose optimistic path calculation unit to connect the destination node without glue logic decisions in routing. PAR XY-X outperforms the Normal XY routing by 20% and 33% with respect to Avg.latency and throughput.